Natural disasters and risk communication implications of the Cascadia subduction zone megaquake - Fletcher, Courtney Vail, 1979-; Lovejoy, Jennette (Environmental Communication and Nature: Conflict and Ecoculture in the Anthropocene, 2018)
Asks and addresses how we communicate about natural disasters and what effect our communication has on natural disaster education, understanding, assessment of risk, preparation, and recovery. The chapters of this book present expertise, analyses, and perspectives that are designed to help us better comprehend and deal with the natural risks such as the Cascadia Subduction Zone. It seeks to move past primal, fear-induced physiological and emotional responses to crises with the understanding that if we accept that the disaster will occur, expect it, and learn how we can prepare, we can calm the collective panicked beats of our hearts as we wait for its first tremors.